STRENGTHENING THE CAPACITY OF POSYANDU (INTEGRATED HEALTH SERVICE POST) CADRES IN UTILIZING THE PANDUREJO APPLICATION FOR DIGITAL-BASED HEALTH DATA AND INFORMATION MANAGEMENT - Rokhayati -; Este Latifahanun (Jurnal Pengabdian Kepada Masyarakat Mulia Madani Yogyakarta, 2026)
The utilization of information technology has become an urgent necessity across various aspects of public service, including the health sector. One application of this technology is the